Pilot Study of Remote Ischemic Conditioning in Acute Spontaneous Intracerebral Hemorrhage - Jarrahi, Abbas; Shah, Manan; Ahluwalia, Meenakshi; Khodadadi, Hesam; Vaibhav, Kumar; Bruno, Askiel; Baban, Babak; Hess, David C.; Dhandapani, Krishnan M.; Vender, John R. (Frontiers in Neuroscience, 2022)
Spontaneous Intracerebral hemorrhage (ICH) is a devastating injury that accounts for 10-15% of all strokes. The rupture of cerebral blood vessels damaged by hypertension or cerebral amyloid angiopathy creates a space-occupying hematoma that contributes toward neurological deterioration and high patient morbidity and mortality. Numerous protocols have explored a role for surgical decompression of ICH via craniotomy, stereotactic guided endoscopy, and minimally invasive catheter/tube evacuation. Studies including, but not limited to, STICH, STICH-II, MISTIE, MISTIE-II, MISTIE-III, ENRICH, and ICES have all shown that, in certain limited patient populations, evacuation can be done safely and mortality can be decreased, but functional outcomes remain statistically no different compared to medical management alone. Only 10-15% of patients with ICH are surgical candidates based on clot location, medical comorbidities, and limitations regarding early surgical intervention. To date, no clearly effective treatment options are available to improve ICH outcomes, leaving medical and supportive management as the standard of care. We recently identified that remote ischemic conditioning (RIC), the non-invasive, repetitive inflation-deflation of a blood pressure cuff on a limb, non-invasively enhanced hematoma resolution and improved neurological outcomes via anti-inflammatory macrophage polarization in pre-clinical ICH models. Herein, we propose a pilot, placebo-controlled, open-label, randomized trial to test the hypothesis that RIC accelerates hematoma resorption and improves outcomes in ICH patients. Twenty ICH patients will be randomized to receive either mock conditioning or unilateral arm RIC (4 cycles x 5 minutes inflation/5 minutes deflation per cycle) beginning within 48 hours of stroke onset and continuing twice daily for one week. All patients will receive standard medical care according to latest guidelines. The primary outcome will be the safety evaluation of unilateral RIC in ICH patients. Secondary outcomes will include hematoma volume/clot resorption rate and functional outcomes, as assessed by the modified Rankin Scale (mRS) at 1- and 3-months post-ICH. Additionally, blood will be collected for exploratory genomic analysis. This study will establish the feasibility and safety of RIC in acute ICH patients, providing a foundation for a larger, multi-center clinical trial.